Creative Resistance and the Territorialization of Collective Action: The Struggle over Eresos Beach, Greece - Zafeiris, Konstantinos; Stavrianoudaki, Elisavet (PARTECIPAZIONE E CONFLITTO, 2026)
This article investigates how a community-based environmental mobilization in Eresos (Lesvos, Greece) turned a localized conflict over beach privatization into durable collective organization and everyday infrastructures of autonomy. Building on social movement scholarship on grassroots and “ad hoc” mobilization, and engaging Holloway’s notion of “cracks” alongside debates on territorialization, the article introduces creative resistance as a process through which negation is converted into sustained social forms. Empirically, the study draws on one year of ethnographic fieldwork conducted by two researchers, combining participant observation (assemblies, beach actions, public interventions, everyday practices) with five semi-structured interviews with long-term participants. The findings show that (1) conflict over Afentelli beach catalyzed a shift from episodic protest to organized community presence (blockade shifts and assemblies); (2) creativity operated as a practical mechanism for sustaining participation and broadening mobilization (cultural events, DIY practices, solidarity initiatives); and (3) institutionalization through the Environmental Association did not “close” mobilization but re-embedded it, enabling continuity, legitimacy, and collective control over resources.